2023
DOI: 10.1029/2022jg007350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Resolution, Mapping Window Size, and Spectral Species Clustering on Remote Sensing of Plant Beta Diversity Using biodivMapR and Hyperspectral Imagery

Abstract: Using imaging spectroscopy (hyperspectral imaging), we assessed the effects of spatial resolution, size of mapping windows composed of pixels, and number of clustered spectral species on the capacity to map plant beta diversity using the biodivMapR package, in support of the planned NASA Surface Biology and Geology (SBG) satellite remote sensing mission. Specifically, we tested the ability of biodivMapR to distinguish natural communities among field‐verified locations. biodivMapR clusters pixels as spectral sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…A moderate number of pixels per parcel not only hampers capturing fine-scale features but also results in an unstable spectral variance (Piovesana and Senior 2018), increasing the susceptibility of spectral diversity to artifacts and noise. Our results align with Robertson et al (2023), which showed that mapping spectral diversity depends on both the spatial resolution and dimensions of the mapping windows. Therefore, we believe that the parcel to pixel size ratio is critical for accurate estimation of plant diversity from space.…”
Section: The Spatial Perspective On the Plant Diversity-spectral Dive...supporting
confidence: 89%
“…A moderate number of pixels per parcel not only hampers capturing fine-scale features but also results in an unstable spectral variance (Piovesana and Senior 2018), increasing the susceptibility of spectral diversity to artifacts and noise. Our results align with Robertson et al (2023), which showed that mapping spectral diversity depends on both the spatial resolution and dimensions of the mapping windows. Therefore, we believe that the parcel to pixel size ratio is critical for accurate estimation of plant diversity from space.…”
Section: The Spatial Perspective On the Plant Diversity-spectral Dive...supporting
confidence: 89%